Atypical Leiomyoma With Features Suggesting of Fumarate Hydratase Mutation. (November 2016) - Wei, Jian-Jun
Abstract : Individuals with germ line or somatic mutations of fumarate hydratase are predisposed to the development of leiomyomas of the skin and uterus. In this case report, we will describe the uterine smooth muscle tumors in a young patient who was originally diagnosed with ALM from a myomectomy specimen and experienced recurrence many years later. Tumor cells are diffusely immunoreactive for 2SC, suggestive of FH mutations.